The C3dg Fragment of Complement Is Superior to Conventional C3 as a Diagnostic Biomarker in Systemic Lupus Erythematosus - Troldborg, Anne; Jensen, Lisbeth; Deleuran, Bent; Stengaard-Pedersen, Kristian; Thiel, Steffen; Jensenius, Jens Christian (Frontiers in Immunology, 2018)
Introduction/Objectives: In 2012, hypocomplementemia was included in the classification criteria of systemic lupus erythematosus (SLE). The suggested measurement of C3 or C4 often reflect disease activity poorly. Our objective was to establish an assay measuring C3dg, which is generated following complement activation, and to evaluate the assay in a cross-sectional SLE cohort. Method: We included SLE patients (n=169) and controls (n=170) and developed a modified C3dg assay where C3dg fragments were separated from the large plasma proteins by polyethylene glycol (PEG), and the supernatant containing the C3dg fragment was used for analysis in an antibody-based sandwich-type assay. Gel permeation chromatography and Western blotting were used to establish the optimal conditions for PEG precipitation. Results: Sixteen % PEG was optimal for separating C3dg from C3 and the larger protein fragments. The assay showed a high degree of stability when using EDTA plasma, and measurements correlated well with commercially available complement activation assays. SLE patients had higher concentrations in plasma of C3dg than controls (p<0.05). ROC analysis showed that the C3dg activation fragment of C3 with an AUC of 0.96 (CI 0.94-0.98) was superior to C3 (AUC 0.52) in differentiating between patients and controls. Conclusions: Our results present a modified assay for the measurement of C3dg. We demonstrate that C3dg was superior to conventional C3 measurements in discriminating SLE patients from controls. We suggest that C3dg should be considered as a complement activation measurement in the SLE classification criteria.